Women Don't Run? Election Aversion and Candidate Entry. Issue 3 (2nd December 2014) - Kanthak, Kristin; Woon, Jonathan
Abstract : To study gender differences in candidate emergence, we conduct a laboratory experiment in which we control the incentives potential candidates face, manipulate features of the electoral environment, and measure beliefs and preferences. We find that men and women are equally likely to volunteer when the representative is chosen randomly, but that women are less likely to become candidates when the representative is chosen by an election. This difference does not arise from disparities in abilities, risk aversion, or beliefs, but rather from the specific competitive and strategic context of campaigns and elections. Thus, we find evidence that women are election averse, whereas men are not. Election aversion persists with variations in the electoral environment, disappearing only when campaigns are both costless and completely truthful.